2018
DOI: 10.1038/s41568-018-0081-9
|View full text |Cite
|
Sign up to set email alerts
|

The lung microenvironment: an important regulator of tumour growth and metastasis

Abstract: Lung cancer is a major global health problem, as it is the leading cause of cancer-related deaths worldwide. Major advances in the identification of key mutational alterations have led to the development of molecularly targeted therapies, whose efficacy has been limited by emergence of resistance mechanisms. US Food and Drug Administration (FDA)-approved therapies targeting angiogenesis and more recently immune checkpoints have reinvigorated enthusiasm in elucidating the prognostic and pathophysiological roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
664
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 813 publications
(680 citation statements)
references
References 287 publications
(247 reference statements)
10
664
1
5
Order By: Relevance
“…By detecting the expression of circRNA in patient tissues and cell lines, we found that circCDR1as expression was enhanced in NSCLC, indicating that high expression of circCDR1as could contribute to the malignancy of NSCLC. Tumor growth and metastasis are the two key regulators of lung cancer malignancy . To investigate the potential value of this circRNA in NSCLC, loss‐of‐function experiments were performed to confirm the anti‐proliferation and anti‐metastasis roles of circCDR1as silencing in NSCLC, which was similar to the previous report by Zhang et al .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…By detecting the expression of circRNA in patient tissues and cell lines, we found that circCDR1as expression was enhanced in NSCLC, indicating that high expression of circCDR1as could contribute to the malignancy of NSCLC. Tumor growth and metastasis are the two key regulators of lung cancer malignancy . To investigate the potential value of this circRNA in NSCLC, loss‐of‐function experiments were performed to confirm the anti‐proliferation and anti‐metastasis roles of circCDR1as silencing in NSCLC, which was similar to the previous report by Zhang et al .…”
Section: Discussionsupporting
confidence: 74%
“…Tumor growth and metastasis are the two key regulators of lung cancer malignancy. 29 To investigate the potential value of this circRNA in NSCLC, loss-of-function experiments were performed to confirm the anti-proliferation and anti-metastasis roles of circCDR1as silencing in NSCLC, which was similar to the previous report by Zhang et al 16 Moreover, epithelial-to-mesenchymal transition has been regarded as an important mechanism involved in the regulation of development and metastasis of lung cancer. 30,31 Hence, whether circCDR1as can promote cell growth, migration and invasion by inducing epithelial-tomesenchymal transition should be explored in the future.…”
Section: Discussionsupporting
confidence: 68%
“…[94] It has been treated as a new target, and many nanodrugs have been designed to respond to the tumor microenvironment, such as acidity and enzyme contents. Understanding the specific conditions of the tumor microenvironment may provide guidance for the treatment of tumors.…”
Section: Tumor Microenvironment-responsive Peptidesmentioning
confidence: 99%
“…Understanding the specific conditions of the tumor microenvironment may provide guidance for the treatment of tumors. [94] It has been treated as a new target, and many nanodrugs have been designed to respond to the tumor microenvironment, such as acidity and enzyme contents. [95] Recently, some specific peptides have been found to respond to the tumor microenvironment, and nanodrugs based on these peptides can undergo changes in the tumor microenvironment, such as structure and shape changes.…”
Section: Tumor Microenvironment-responsive Peptidesmentioning
confidence: 99%
“…Despite these technological advances, deep understanding of molecular mechanisms underlying development of complex lung pathologies is hindered by the heterogeneity of the lung microenvironment 20 and by changes in cellular number and composition during disease progression 14 , which cannot be resolved with bulk tissue studies. Hence, NGS-based approaches providing cellular resolution, like profiling of defined cell populations or single-cell analyses need to be implemented in order to identify cell types driving distinct disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%